2009
DOI: 10.1016/j.nutres.2009.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Both human immunodeficiency virus–infected and human immunodeficiency virus–exposed, uninfected children living in Brazil, Argentina, and Mexico have similar rates of low concentrations of retinol, β-carotene, and vitamin E

Abstract: Our objective was to describe the prevalence of low concentrations of retinol, β-carotene, and vitamin E in a group of HIV-infected Latin American children and a comparison group of HIV-exposed, uninfected children. Our hypothesis was that the rates of low concentrations of these micronutrients would be higher in the HIV-infected group than those in the HIV-exposed, uninfected group. This was a cross-sectional substudy of a larger cohort study at clinical pediatric HIV centers in Latin America. Serum levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 45 publications
(40 reference statements)
0
13
1
1
Order By: Relevance
“…Infants in our sub-study had lower rates of micronutrient defi ciencies and higher mean levels of vitamin A and vitamin E than those found by Monteiro et al in a group of HIV-infected Latin American children 14 . Nevertheless, 81% of infants at birth were defi cient in α-tocopherol, which could partially be explained by increased oxidative stress during delivery.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Infants in our sub-study had lower rates of micronutrient defi ciencies and higher mean levels of vitamin A and vitamin E than those found by Monteiro et al in a group of HIV-infected Latin American children 14 . Nevertheless, 81% of infants at birth were defi cient in α-tocopherol, which could partially be explained by increased oxidative stress during delivery.…”
Section: Discussioncontrasting
confidence: 58%
“…Lower levels of vitamin E may play a pathogenic role in the onset and development of acquired immunodefi ciency syndrome (AIDS) and other infectious diseases 10,11 . Several studies have revealed lower vitamin E levels in HIV-infected children in Brazil and elsewhere [12][13][14] . Among healthy pregnant women, infant birth weight and length are associated with maternal serum concentrations of antioxidant vitamins 15 .…”
mentioning
confidence: 99%
“…Deficiencies of these micronutrients have been related to an accelerated progression of HIV, since they compromise the function of T and B cells, increasing the incidence and severity of the infection (5,6). Vitamin A increases the function of natural killer cells in vitro and supplementary doses of vitamin A alter the phagocytic cell response by stimulating phagocytosis and cell-mediated cytotoxicity (7).…”
mentioning
confidence: 99%
“…According to a systematic review (9), vitamin A supplementation is beneficial and safe in HIV-infected children, although its role in HIV-infected adults is not clear. Observational studies (6,10) found that beta-carotene concentrations were significantly lower in HIV patients. Several properties of this micronutrient supported the hypothesis that it could influence HIV disease, including its importance in maintaining normal immune responses, its ability to act as an antioxidant, and its role as a provitamin A molecule.…”
mentioning
confidence: 99%
“…A albumina plasmática em concentrações ideais corrobora estudo feito com 1.240 crianças expostas ao vírus, sendo 124 infectados, que apresentavam níveis séricos de albumina normais 23 ; assim como estudo realizado com 38 crianças de 2 a 11 anos, sendo 10 infectadas pelo HIV com atraso no crescimento, 18 infectadas pelo HIV com crescimento normal e 10 sem infecção com crescimento normal 24 .…”
Section: Tabela 4 -unclassified